A conceptual framework for process‐oriented employee appraisals and rewards. (22nd June 2020) - Shafagatova, Aygun; Van Looy, Amy
Abstract : This study aims to translate generic human resource management (HRM) appraisals and rewards toward an organization's business processes for better aligning organizational practices to a process orientation and for a successful business process management (BPM) adoption. We conducted an interdisciplinary study with three phases. Firstly, we conducted a literature study to obtain a list of typical business process characteristics that can be relevant for HRM appraisals and rewards. Secondly, we used an expert panel to validate and refine this list. Finally, we integrated those concepts into generic theories and frameworks on HRM appraisals and rewards through a translation study. We provide a conceptual framework of process‐oriented HRM appraisals and rewards that integrates HRM and BPM concepts. The framework presents process‐specific characteristics to supplement generic HRM appraisals and rewards frameworks. Given the challenges of aligning function‐based appraisals and rewards to a business process orientation, the framework can help tackle interdisciplinary challenges and brings a high‐level understanding of what to focus on during this alignment.